2012
DOI: 10.1007/s00348-012-1306-4
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic drag reduction of a simplified squareback vehicle using steady blowing

Abstract: Citation: LITTLEWOOD, R.P. and PASSMORE, M.A., 2012. Aerodynamic drag reduction of a simplified squareback vehicle using steady blowing. Experiments in Fluids, 53(2), pp. 519 -529.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 12 publications
2
64
0
Order By: Relevance
“…The origin of this relationship can be ascribed to the reduction of the interaction between the recirculating structures and the base occurring any time the wake switches from a bi-stable state to a symmetric state, resulting in a 7% decrease of the base drag compared to the time-averaged value. This potential gain motivates the application of flow control strategies aiming to stabilising the symmetric state, as proposed for example by Grandemange et al (2014b), Evrard et al (2016), Li et al (2016), and Brackston et al (2016) and suggests the existence of an additional margin for improvement in those cases where the actuated flow is still asymmetric, as in Littlewood and Passmore (2012) and Barros et al (2016). Furthermore, the results of the findings presented in this work seem to suggest that a certain degree of pumping motion is "needed" to trigger a switch when the wake is in a condition of "almost perfect symmetry", but is not enough when the system is forced towards one of the laterally asymmetric states (for example by yawing the model).…”
Section: Discussionmentioning
confidence: 99%
“…The origin of this relationship can be ascribed to the reduction of the interaction between the recirculating structures and the base occurring any time the wake switches from a bi-stable state to a symmetric state, resulting in a 7% decrease of the base drag compared to the time-averaged value. This potential gain motivates the application of flow control strategies aiming to stabilising the symmetric state, as proposed for example by Grandemange et al (2014b), Evrard et al (2016), Li et al (2016), and Brackston et al (2016) and suggests the existence of an additional margin for improvement in those cases where the actuated flow is still asymmetric, as in Littlewood and Passmore (2012) and Barros et al (2016). Furthermore, the results of the findings presented in this work seem to suggest that a certain degree of pumping motion is "needed" to trigger a switch when the wake is in a condition of "almost perfect symmetry", but is not enough when the system is forced towards one of the laterally asymmetric states (for example by yawing the model).…”
Section: Discussionmentioning
confidence: 99%
“…A quarter scale Windsor Model, Figure 1, as used in [4,7,8,14,15] was used for this work. The model is constructed of a machinable model board and gives a blockage ratio of 4.4% in the 2.5m 2 working section.…”
Section: Modelmentioning
confidence: 99%
“…The use of two component, two dimensional PIV is well documented in a variety of situations [4,7,8,9,10] and traditionally involves a single camera that is normal to the measurement plane, a pulsed laser passing through a plano-concave lens to create a diverging sheet of light focused to a thickness of around 1mm, neutrally buoyant seeding particles (such as DEHS solution which has been atomized to form 1μm particles) and a computer containing a timing board that allows for the control of the system. This technique is particularly accurate when there is only a small amount of through plane motion so that the majority of the particles captured by the camera in the double frame image pair remain within the light sheet.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years active flow control techniques have been of research interest due to their potential ability to achieve flow modification and drag reductions without the need for physical shape changes, however they have yet to be proven in a real world vehicle application. Previous experiments using the Windsor reference model and steady blowing (6) as a means of flow control have found large reductions in drag forces, that arise through modification of the wake structure to create an increase in base pressure. Littlewood (6) reported that the mechanisms that appear to be important in these changes might also be effected through passive modifications.…”
Section: An Investigation Into the Wake Structure Of Square Back Vehimentioning
confidence: 99%
“…Previous experiments using the Windsor reference model and steady blowing (6) as a means of flow control have found large reductions in drag forces, that arise through modification of the wake structure to create an increase in base pressure. Littlewood (6) reported that the mechanisms that appear to be important in these changes might also be effected through passive modifications. Therefore the current work uses passive techniques with the aim of modifying the wake structure and are used as a means of understanding how flow mechanisms and structures within the wake of a squareback vehicle can influence drag forces.…”
Section: An Investigation Into the Wake Structure Of Square Back Vehimentioning
confidence: 99%